1996
DOI: 10.1021/bi960190j
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Ribonucleotide Reductase by (E)-2‘-Fluoromethylene-2‘-deoxycytidine 5‘-Diphosphate:  A Paradigm for Nucleotide Mechanism-Based Inhibitors

Abstract: Ribonucleotide reductase (RDPR) from Escherichia coli catalyzes the conversion of nucleotides to deoxynucleotides and is composed of two homodimeric subunits: R1 and R2. (E)- and (Z)-2'-fluoromethylene-2'-deoxycytidine 5'-diphosphate (FMCDP) are time dependent inactivators of this protein, with approximately 1.5 equiv being sufficient for complete loss of catalytic activity. Inactivation results from loss of the essential tyrosyl radical on R2 and alkylation of R1. Studies using electron spin resonance spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
98
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(104 citation statements)
references
References 43 publications
6
98
0
Order By: Relevance
“…By contrast, previous studies with bacterial ribonucleotide reductase have shown that 2Ј-substituted diphosphate nucleosides may directly interfere with the RRM1 subunit. In fact, a 2Ј-fluoro-methylenyl derivative appears to form a covalent interaction with RRM1 from Escherichia coli that permanently inactivates that subunit (21). The physical relationship between gemcitabine and mammalian ribonucleotide reductase has not been well characterized, however, data support the hypothesis that the RRM1 subunit is the most likely intracellular target of gemcitabine diphosphate (22).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, previous studies with bacterial ribonucleotide reductase have shown that 2Ј-substituted diphosphate nucleosides may directly interfere with the RRM1 subunit. In fact, a 2Ј-fluoro-methylenyl derivative appears to form a covalent interaction with RRM1 from Escherichia coli that permanently inactivates that subunit (21). The physical relationship between gemcitabine and mammalian ribonucleotide reductase has not been well characterized, however, data support the hypothesis that the RRM1 subunit is the most likely intracellular target of gemcitabine diphosphate (22).…”
Section: Introductionmentioning
confidence: 99%
“…Crucial for rapidly dividing cells, RR is an attractive therapeutic target of cancer, and over the past years, many chemotherapeutics inhibiting different subunits of RR have been developed and tested clinically for their anticancer activities and anti-HIV activities. [10][11][12][13] HU is the first RR inhibitor applied to the clinic, and is utilized for the therapeutic of neoplasms because of its influences on the DNA replication of cancer cells. 1,14) To overcome the drawbacks of HU, numerous medicinal chemistry efforts have been made to design and synthesize novel HU derivatives.…”
Section: Synthesis and Anticancer Evaluation Of Benzyloxyurea Derivatmentioning
confidence: 99%
“…Early studies demonstrated that the diphosphate of this compound affects ribonucleotide reductase through a mechanism-based inhibition (van der Donk et al, 1996) similar to that of gemcitabine. However, unlike gemcitabine and 1-␤-D-arabinofuranosylcytosine, FMdC is relatively resistant to deamination by cytidine deaminase .…”
mentioning
confidence: 99%
“…The inhibition of ribonucleotide reductase by FMdC diphosphate has been well characterized (van der Donk et al, 1996;Kanazawa et al, 1998). In vitro studies suggest that the triphosphate of FMdC may inhibit human DNA polymerase (pol) ␣ and cause a pause in further DNA synthesis (Yonetani and Mizukami, 1996).…”
mentioning
confidence: 99%